2002
DOI: 10.1080/09620210200200087
|View full text |Cite
|
Sign up to set email alerts
|

Teaching in the dark: The geopolitical knowledge and global awareness of the next generation of American teachers

Abstract: This study examines the geopolitical knowledge and global awareness of American upper-level undergraduate university students in a large teacher education program. The context for the study involves the educational implications to which scholars and policy-makers increasingly call attention. Many of the perceived implications of globalization suggest a challenging and significant role for teachers in a time of change. On measures of geopolitical knowledge, awareness of prominent international leaders and organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 7 publications
0
15
0
2
Order By: Relevance
“…Teaching political issues encounters difficulties and barriers in various places around the world (Grayson 2015). For example, a study examining the knowledge and understanding of geopolitical teaching in the US at the beginning of this century shows that there is a lack of attention and awareness surrounding geopolitical issues (Holm & Farber 2002). The researchers found that although understanding geopolitical processes was significant for teachers in times of change (the article was written one year after September 11, 2001), the knowledge they demonstrated was poor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teaching political issues encounters difficulties and barriers in various places around the world (Grayson 2015). For example, a study examining the knowledge and understanding of geopolitical teaching in the US at the beginning of this century shows that there is a lack of attention and awareness surrounding geopolitical issues (Holm & Farber 2002). The researchers found that although understanding geopolitical processes was significant for teachers in times of change (the article was written one year after September 11, 2001), the knowledge they demonstrated was poor.…”
Section: Methodsmentioning
confidence: 99%
“…The geopolitical issues examined relate to the international economy and international markets, the power of countries, cooperation between countries, multicultural cooperation (e.g., the Olympics reflects the need for cooperation among nations), as well as environmental issues such as climate change and environmental sustainability, human rights, migration, and population growth. The researchers found that the source from which the respondents gained most of their knowledge was not the education system but from the media (Holm & Farber 2002). In Europe, the contents of the study were examined, and it was found that the perception of "European integration" is derived from a national point of view in each country, and that the textbooks serve as "vehicles of nationalism" (Sakki 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Many countries even mandate English learning at schools to help their citizens better understand the United States and the Western world. Americans, on the contrary, seem to know relatively little about other nations and their cultures (Asia Society 2001;Holm and Farber 2002;Lindaman and Ward;RoperASW for National Geographic Education Foundation 2002). Dana Lindaman and Kyle Ward (2004) argued that this isolationist tendency is most apparent within the U.S. educational system because social studies, particularly history textbooks, typically deal with national and world history from a political and patriotic perspective, and American students are rarely exposed to different perspectives in the classroom.…”
Section: -Participantmentioning
confidence: 96%
“…This is a difficult task as the scientific evidence about global biodiversity and its loss is rather uncertain and often controversial (Kassas, 2002). To adequately teach this complex issue, teachers need a basic understanding about the world, its principal regions and political and biogeographic characteristics (Holm and Farber, 2002). In line with other authors, we argue that teaching about a complex and controversial issue, such as the distribution and loss of biodiversity, raises important questions for teachers concerning bias, balance and personal worldviews (e.g., Pajares, 1992; Holm and Farber, 2002; Moseley and Utley, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To date, researchers have been predominantly focused on student teachers’ understanding of the terminology and socio-scientific aspects of biodiversity issues (Gayford, 2000; Summers et al, 2004; Kyburz-Graber et al, 2006; Lindemann-Matthies et al, 2011). Besides these important aspects, the global dimension of the distribution and loss of biodiversity is often depicted as a major educational challenge for both teachers and learners alike (Bybee, 1991; Chiodo, 1993; Merryfield, 2000; Hicks and Bord, 2001; Holm and Farber, 2002; Bolscho and Hauenschild, 2006; Scheunpflug and Asbrand, 2006; Menzel and Bögeholz, 2008; Lindemann-Matthies et al, 2009). With regards to the student teachers’ worldviews and perceptions of the global dimension of biodiversity and its loss, a sound empirical basis is still lacking.…”
Section: Introductionmentioning
confidence: 99%